The Moral Embeddedness of Markets - Jens Beckert (Max Planck Institute for the Study of Societies, 2005)
This paper addresses the question of what role morally oriented behavior plays in the efficiency of market outcomes. This issue is as controversial in economics as it is in sociology. To get a better understanding of the problems and opportunities involved in morally oriented behavior in markets, I develop a typology that distinguishes four different forms of morality-based behavior and try to understand what consequences derive from these types of morally motivated action. The four forms I discuss I call 'cooperation', 'group solidarity', 'blocked exchange' and 'altruism'. There is a fifth - 'parasitic' - type that I call 'Trojan altruism'. I argue that the contested role of morality is rooted in the profoundly ambivalent consequences that morality has on market efficiency. – – In diesem Discussion Paper betrachte ich die Auswirkungen moralisch orientierten Handelns auf die Effizienz von Märkten. Diese Frage ist sowohl unter Soziologen als auch unter Ökonomen stark umstritten. Um zu einem besseren Verständnis der Probleme und Chancen zu gelangen, die sich aus moralischen Handlungsorientierungen für Marktbeziehungen ergeben, entwickele ich eine Typologie, mit der vier verschiedene Formen moralgestützten Handelns unterschieden werden. Die vier Formen nenne ich 'Kooperation', 'Gruppensolidarität', 'blockierter Tausch' und 'Altruismus'. Darüber hinaus besteht ein fünfter, parasitärer Typus, den ich als 'Trojanischen Altruismus' bezeichne. Ich zeige, dass die umstrittene Rolle von Moralität für Märkte ihren Hintergrund in den tatsächlich zutiefst ambivalenten Folgen von Moralität für die Effizienz von Märkten hat.
Keywords: 300